Pembangunan Agro-Ekowisata Terpadu Di Desa Aan, Klungkung-Bali - Sutiarso, Moh Agus; Suprapto, I Nyoman Arto; Wijaya, I Made Agus Hendra (Yayasan Kajian Riset dan Pengembangan RADISI, 2023)
The community service program for the Community Science and Technology Implementation (PIM) scheme is located in Aan village, Klungkung, Bali. The problem faced by the program's target partners (Pokdarwis) is the lack of knowledge and skills of Pokdarwis (Aan Village Tourism Awareness Group )members in managing tourism potential in their area based on agro-ecotourism. The solution that has been implemented is to provide assistance in rural tourism governance, and assistance in creating superior tourism packages, as well as assistance in making interpretive materials for tourism activities based on agro-ecotourism. The outputs that have been achieved include: 1) Creation of superior tour packages, namely trekking on Batu Kembar Hill, Secret Waterfall tour, and cycling tour around Aan Village; 2) Increasing promotional means in the form of content that specifically promotes agro-ecotourism based tourism. The trekking tour package in the Aan tourist village is popular with tourists and has an impact on Pokdarwis' income and the Aan tourist village is becoming increasingly well known. From the results of community service which the people of Aan village responded positively and enthusiastically, it is hoped that the program will continue.